2015
DOI: 10.1007/s12272-015-0655-y
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoid composition and the anticancer activity of Acanthopanax trifoliatus

Abstract: The petroleum ether and ethyl acetate fractions of extract from an edible and medicinal plant Acanthopanax trifoliatus were found to show significant inhibitory effects against SF-268, MCF-7, HepG2 and NCI-H460 cancer cells. Two new ursane-type triterpenoids, acantrifoic acid C (1) and acantrifoic acid D (2), along with five known triterpenoids (3-7) and eight known diterpenoids (8-15) were obtained from these two fractions. To the best of our knowledge, this is the first report concerning the isolation of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Our team found that AT extracts had anticancer activities in prostate cancer cells, neural cancer cells, breast cancer cells, liver cancer cells, and large cell lung cancer cells. We also provided evidence that AT terpenoids exert anticancer activities, indicating that AT may be a useful edible plant for further development as a health supplement (Li et al., 2016).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our team found that AT extracts had anticancer activities in prostate cancer cells, neural cancer cells, breast cancer cells, liver cancer cells, and large cell lung cancer cells. We also provided evidence that AT terpenoids exert anticancer activities, indicating that AT may be a useful edible plant for further development as a health supplement (Li et al., 2016).…”
Section: Introductionmentioning
confidence: 76%
“…It has been reported that A trifoliatus (L.) Merr. contains diverse active constituents of saponins and polyphenols contributing to the beneficial biological effects, including antioxidant (Sithisarn, Muensaen, et al., 2016), anti‐inflammatory (Sithisarn, Muensaen, et al., 2016), and anticancer activities (Li et al., 2016). Among them, the flavonoids are important material basis in polyphenols for bio‐activities.…”
Section: Resultsmentioning
confidence: 99%
“…are used as tonics and sedatives for treating rheumatism and diabetes, 16 and the young leaves and shoots are often consumed as tea and vegetables. 17 Studies show that A. trifoliatus (L.) Merr. extracts have anti-cancer, 18 anti-inflammatory, 19 and anti-depressant effects, 20 although a hypoglycemic activity has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that more than one half of all cancer cases and deaths worldwide are potentially preventable and one strategy with enormous potential of use to deal with this issue is chemoprevention (American Cancer Society, 2011). A number of natural agents present in foods such as, flavonoids, carotenoids, isothiocyanates, terpenoids, and omega-3 fatty acids, have been evaluated for their anticancer effect in early stages of carcinogenesis (Vidak et al, 2015;Lawson et al, 2015;Li et al, 2016;López-Saiz et al, 2014;Rovito et al, 2013). However, the oceanic environment has been recognized as a wide source of natural bioactive compounds with pharmacological potential and possible future applications (Montaser & Luesch, 2011).…”
Section: Introductionmentioning
confidence: 99%